Joint probability for evaluating the schedule and cost of stochastic simulation models. Issue 3 (August 2015) - Mawlana, Mohammed; Hammad, Amin
Abstract The review of construction engineering and management literature shows that the occurrence of multi-performance indices in stochastic simulation models have been treated the same way as the occurrence of a single performance index. By doing so, the correlation between these indices and the impact they have on each other are ignored. Their occurrences have been treated as disjoint, which leads to errors in evaluating the probabilities of the performance indices of these models. The objectives of this paper are to present a new method that can: (1) quantify the impact of uncertainty on the project schedule and cost simultaneously; (2) calculate the conditional probability of the project cost given a specific project duration, and vice versa; (3) find the best project duration and cost that meet a specific joint probability; (4) estimate the project schedule and cost joint contingency using joint probability; and (5) generate a schedule representing a specific joint probability. The paper presents the implementation details and several case studies to demonstrate the feasibility of the proposed method. The proposed method shall provide a more accurate analysis to the output of stochastic simulation.